Colistin sulfate versus polymyxin B for the treatment of infections caused by carbapenem-resistant Acinetobacter baumannii: a multicenter retrospective cohort study - Liu, Hongmei; Tang, Li; Zheng, Liang; Fu, Yuanyuan; Qian, Mingjiang; Ouyang, Canghong; Tao, Na; Ou, Shuiping; He, Yong (Frontiers in Pharmacology, 2025)
BackgroundPolymyxins are the last line of defense against carbapenem-resistant Gram-negative bacilli infections. However, the efficacy of polymyxins against the independent risk factor of bacterial species is unknown. We aimed to compare the efficacy and safety of colistin sulfate (CS) and polymyxin B (PMB) for carbapenem-resistant Acinetobacter baumannii (CRAB) infections.MethodsWe carried out a retrospective multicenter study that included patients with CRAB infections at three tertiary hospitals in Guizhou province, China, from 1 Jan 2020 to 30 Jun 2024. Patients were grouped into the CS group and PMB group. The main outcomes were all-cause 28-day mortality and clinical failure rate. The secondary outcomes included the microbiological cure rate, duration of CS or PMB treatment, and length of hospital stay. Safety was evaluated based on the rates of adverse drug reactions.ResultsA total of 140 patients were included, with 58 patients in the CS group and 82 patients in the PMB group. All-cause 28-day mortality was 32.8% in the CS group and 37.8% in the PMB group (adjusted HR = 0.73, 95% CI 0.38–1.37, p = 0.316), and the clinical failure rate was 48.3% and 56.1% (adjusted OR = 0.64, 95% CI 0.29–1.39, p = 0.262) in the CS group and PMB group, respectively. There were no significant differences in any of the secondary outcomes. The incidence of acute kidney injury (AKI) in the CS group was lower than that in the PMB group (5.2% vs. 19.5%). Compared to the PMB group, the adjusted odds ratio of AKI was 0.24 (95% Cl 0.06–0.96, p = 0.044) for the CS group.ConclusionOur results suggest that CS is similarly effective to PMB for CRAB infections but it is associated with fewer safety concerns than PMB. This clinical research provides significant information on the efficacy and safety of CS and PMB for CRAB infections.